Emotional Contagion or Symbolic Cognition? A Social Identity Perspective on Media Events. Issue 1 (2nd January 2018) - Cui, Xi
Abstract : This study aims to understand the psychological mechanisms of the generation of viewers' emotional reactions in successful media events and the role of social identity in the process. An online survey was conducted among Chinese viewers shortly after an important national ceremony was broadcast in China. A direct route between viewers' media consumption and emotional arousal and a mediated route between them through cognition of the symbolism in the event were found. However, high-nationalist viewers were only aroused through symbolic cognition, while low-nationalist viewers gained emotions through both the direct and the indirect routes. The findings suggest two psychological mechanisms of ritual communications moderated by social identities and clarify the role of social identity in media ritual theories.